Diametrical tensile strength test of dental bioactive cement: Uji kekuatan tarik diametral semen bioaktif dental - Angela Evelyna; Dian Lesmana; Grace Monica; Fathul Mauludy (Makassar Dental Journal, 2022)
Introduction: Bioactive dental cement material is widely used in root canal treatment in order to provide long lasting result of the root canal treatment. The test ofmechanical properties on this bioactive dental cement material is a diametrical tensile test. The purpose of this study was to examine the diametrical tensile strength (DTS) of bioactive dental cement materials found in Indonesia. Methods: Specimens of bioactive dental cement material are disc-shaped, 6 mm in diameter, 3 mm in height which were divided into 2 groups; Group I is Maarc MTA and Group II is MTA plus white cerkamed, each group contains 4 speci-mens. Mechanical properties test was carried out using Universal Testing Machine (UTM), analyzed with one-way Anova. Re-sults: The DTS mean of Group Iwas 2.48564 N/mm2 and Group II of 7.872175 N/mm2; significantly different (f count: 0.065). Conclusion: MTA white plus cerkamed has higher DTS than Maarc MTA.